2018
DOI: 10.1016/j.fuproc.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rheological properties of mesophase pitch and coal mixtures on pore development in activated carbon discs with high compressive strength

Abstract: We measured the rheological properties of mesophase pitch + coal mixtures at temperatures up to 873 K and used quench tests during carbonization to observe the effects of coal particles on foaming and pore development in activated carbon discs (ACD). We observed that high ratios of coal to pitch increased the mixture's viscosity in a low pressure foaming process, which restricted growth of large bubbles during foaming and produced stronger carbon foams. The highest strength ACD, with compressive strength of 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
20
0
1
Order By: Relevance
“…Since the physical performance and chemical composition of precursor have a significant impact on the cell shape, size and their distribution of resulting foams and corresponding mechanical properties, the PR is proposed to modify the foams’ precursor [16,26,27,34]. Figure 4 shows the SEM images of the cross-sectional morphologies of the pristine CF and mCF-1, mCF-3, mCF-5, mCF-7 and mCF-9, where the additive amount of PR is 1 wt%, 3 wt%, 5 wt%, 7 wt% and 9 wt%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the physical performance and chemical composition of precursor have a significant impact on the cell shape, size and their distribution of resulting foams and corresponding mechanical properties, the PR is proposed to modify the foams’ precursor [16,26,27,34]. Figure 4 shows the SEM images of the cross-sectional morphologies of the pristine CF and mCF-1, mCF-3, mCF-5, mCF-7 and mCF-9, where the additive amount of PR is 1 wt%, 3 wt%, 5 wt%, 7 wt% and 9 wt%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this issue, three methods have been developed in the last few decades to optimize the cell distribution and the mechanical performance of resulting CF [25], such as (1) regulate the foaming and carbonization conditions in the process of foaming; (2) modify the precursors by adding the cross-linking agent or modifier for optimizing the chemical composition and fluidity of precursor; (3) incorporate reinforcements into the precursor as graphite [26], coal powder [27], clay-montmorillonite [28], carbon nanotube [29,30], graphene [31], carbon filler [32] and ferrocene [33]. In contrast to the methods for adjusting the foaming condition and choosing reinforcements for the preparation of CF, the chemical modification was proposed due to its operability for modulating physical properties and chemical composition of precursor with low-costs [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Свойства УВ во многом определяются составом использованного пека, так, например для получения волокон с улучшенными параметра-ми, изотропный пек (каменноугольный и нефтяной) должен быть преобразован в мезофазный пек содержащий как анизотропную фазу так и графитовую структуру [32]. Для получения мезофазного пека используют различные методы такие как, пиролиз [33], дистилляция [34], экстракция растворителем [35] или катализатором [36]. Полученные волокна-предшественники из мезофазного пека подвергаются термостабилизации и карбонизации при высоких температурах [30].…”
Section: углеродные волокнаunclassified
“…5,6 As a result, the formation and reaction mechanism of the petroleum-based mesophase pitch are the research priorities for high-value utilization of heavy oil and production of carbon materials. 7,8 Numerous research studies have been performed to study the effects of molecular structure and composition of raw material on the rheological properties, polarized structure and liquid-crystal structure of the carbonized product. [9][10][11] Menéndez et al 11 have suggested that the molecular composition of feedstock had an important inuence on the properties of mesophase product by investigating the structural relationship of petroleum pitches and their condensation products.…”
Section: Introductionmentioning
confidence: 99%